Quantification of unintegrated HIV-1 DNA at the single cell level in vivo. - Rodolphe Suspène; Andreas Meyerhans (PLoS ONE, 2012)
In the nucleus of HIV-1 infected cells, unintegrated HIV-1 DNA molecules exist in the form of one and two LTR circles and linear molecules with degraded extremities. In tissue culture they are invariably more numerous than the provirus, the relative proportion of integrated to unintegrated forms varies widely from ∼1:1 to 1:10 and even over 1:100. In vivo, this ratio is unknown. To determine it, single nuclei from two infected patients with a known provirus copy number were microdissected, HIV DNA was amplified by nested PCR, cloned and individual clones sequenced. Given the extraordinary sequence complexity, we made the assumption that the total number of distinct sequences approximated to real number of amplifiable HIV-1 DNA templates in the nucleus. We found that the number of unintegrated DNA molecules increased linearly with the proviral copy number there being on average 86 unintegrated molecules per provirus.